Al-Tadrībāt al-Lughawiyyah al-Mushawwiqah fī Taʿlīm al-Lughah al-ʿArabiyyah ʿalā Ḍawʾ Mahārat al-Kitābah - yoke suryadharma (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
Language exercises are among the most essential means of developing language proficiency, as language learning fundamentally requires continuous practice and repeated training. As commonly expressed in English,